Inside conducting - Seaman, Christopher 1942- (Univ. of Rochester Press, 2013)
What does a conductor actually do? How much effect does he or she have? Can the orchestra manage without one? Why don't the players look at the conductor more? Is it necessary for the conductor to play every instrument? What about interpretation? What happens at rehearsals? Why do some conductors "thrash around" more than others? Who's the boss in a concerto: the soloist or the conductor?BR> These are some of the questions that receive lively and informative answers in this book by renowned conductor Christopher Seaman. Composed of short articles on individual topics, it is accessible and easy to consult. Each article begins with an anecdote or saying and ends with quotations from musicians, often expressing opposing views. There are many books on the art of conducting, but none like this. Music lovers wondering what the figure on the podium actually does, and aspiring conductors eager to learn more about the art and craft of leading an orchestra, will all treasure this wise yet humorous book. - Christopher Seaman has been successful at both ends of the baton. After four years as principal timpanist of the London Philharmonic Orchestra, he was appointed principal conductor of the BBC Scottish Symphony Orchestra and has enjoyed a busy international conducting career for over forty years. He is now Conductor Laureate for Life of the Rochester Philharmonic Orchestra, New York, and he continues to bring great music and wise words to audiences, students, and readers around the world.